China's Footprint in Global Commodity Markets - Kolerus, Christina; N'Diaye, Papa.; Saborowski, Christian (Washington, D.C. : International Monetary Fund, 2016)
This note assesses empirically the role Chinese activity plays in global commodities markets, showing that the strength of China's economic activity has a significant bearing on commodity prices, but that the impact differs across commodity markets, with industrial production shocks having a substantial impact on metals and crude oil prices and less so on food prices. The size of the impact on the prices of specific commodities varies with China's footprint in the market for those commodities; the empirical estimates indicate that, over a one-year horizon, a 1 percent increase in industrial production leads to a 5-7 percent rise in metals and fuel prices. The surprise component in Chinese industrial production announcements has a bearing on commodity prices that is comparable in magnitude to that of industrial production surprises in the United States, and this impact is much larger when global risk aversion is high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet